Catalytic effect of praseodymium oxide additive on the microstructure and electrical property of graphite anode. (December 2015) - Wang, Rongyan; Lu, Guimin; Qiao, Wenming; Sun, Ze; Zhuang, Haizheng; Yu, Jianguo
Abstract: Based on the revealed interactions (dissociation energy) between several typical metals (transition and rare-earth elements) and carbon atoms through the DFT quantum mechanics method, Pr can be predicted to possibly be a new potential catalyst. Indeed, Praseodymium oxide (Pr6 O11 ) was insightfully found to catalyze the graphitization more efficiently than the other selected additives. The effects of Pr6 O11 catalyst on the microstructure of the graphite anode were investigated by XRD, Raman spectroscopy, SEM, and TEM. The results indicate that Pr6 O11 addition remarkably improves the formation of crystallites, thereby largely enhancing the electrical property of graphite anode. The graphite anode with a low electrical resistivity of 5.0 μΩ m was successfully available by adding 3 wt. % Pr6 O11 at 2800 °C. Finally, the catalytic graphitization mechanism of rare-earth element was proposed based on the experimental results.